COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF PHARMACEUTICAL COMPANIES DURING AND AFTER THE COVID-19 PANDEMIC - Natsir, Khairina; Bangun, Nurainun (Graduate Program of Universitas Tarumanagara, 2025)
The goal of this study is to evaluate the financial performance differences of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the COVID-19 pandemic (2020-2021) and after the pandemic (2022-2023). The research focuses on five main financial performance indicators: profitability, leverage, liquidity, efficiency, and company growth. Profitability is measured using Return on Assets (ROA) and Net Profit Margin (NPM), leverage through Debt to Equity Ratio (DER), liquidity through Current Ratio (CR), efficiency using Total Asset Turnover (TATO), and company growth through Sales Growth. The sample consists of 11 pharmaceutical companies listed on the IDX. Financial performance data before and after the pandemic will be analyzed using the paired sample t-test method to assess whether there is a significant difference between the two periods. This study aims to provide insights into the long-term effects of the COVID-19 pandemic on the financial performance of pharmaceutical companies in adapting to changes post-pandemic. The findings show no significant difference in ROA, NPM, CR, TATO, and Sales Growth between the pandemic period (2020-2021) and the post-pandemic period (2022-2023), though there is a difference in DER performance between the two periods.